Application of plastic-damage multidirectional fixed smeared crack model in analysis of RC structures. (15th October 2016) - Edalat-Behbahani, A.; Barros, J.A.O.; Ventura-Gouveia, A.
Highlights: A constitutive model for the nonlinear behaviour of concrete structures is proposed. Cracking of concrete is simulated by a multidirectional fixed smeared crack model. A plastic-damage approach is used to account for inelastic compressive behaviour. Potentialities of the proposed model for analysis of RC structures are highlighted. Sensitivity of the simulations to the values of the model parameters is assessed. Abstract: This paper describes a plasticity-damage multidirectional fixed smeared cracking (PDSC) model to simulate the failure process of concrete and reinforced concrete (RC) structures subjected to different loading paths. The model proposes a unified approach combining a multidirectional fixed smeared crack model to simulate the crack initiation and propagation with a plastic-damage model to account for the inelastic compressive behaviour of concrete between cracks. The smeared crack model considers the possibility of forming several cracks in the same integration point during the cracking process. The plasticity part accounts for the development of irreversible strains and volumetric strain in compression, whereas the strain softening and stiffness degradation of the material under compression are controlled by an isotropic strain base damage model. The theoretical aspects about coupling the fracture, plasticity, and damage components of the model, as well as the model appraisal at both material and structural levels, have been detailed in a former publication. This study briefly summarizes the model formulations, and is mainly dedicated to further explore the potentialities of the proposed constitutive model for the analysis of concrete and RC structures. The model is employed to simulate experimental tests that are governed by nonlinear phenomenon due to simultaneous occurrence of cracking and inelastic deformation in compression. The numerical simulations have predicted with good accuracy the load carrying capacity, ductility, crack pattern, plastic (compressive) zone, and failure modes of all types of structures analysed. The influence of the model parameters that simulate the nonlinear behaviour of concrete under tension and compression is analysed through a parametric study.